2021
DOI: 10.1021/acsabm.0c01324
|View full text |Cite
|
Sign up to set email alerts
|

A Bioconjugated Chlorin-Based Metal–Organic Framework for Targeted Photodynamic Therapy of Triple Negative Breast and Pancreatic Cancers

Abstract: The field of photodynamic therapy (PDT) has continued to show promise as a potential method for treating tumors. In this work, a photosensitizer (PS) has been delivered to cancer cell lines for PDT by incorporation into the metal–organic framework (MOF) as an organic linker. By functionalizing the surface of MOF nanoparticles with maltotriose, the PS can efficiently target cancer cells with preferential uptake into pancreatic and breast cancer cell lines. Effective targeting overcomes some current problems wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…MAHfMOF-PFP-Ni-Zn and MA-HfMOF-PFC-Ni-Zn displayed low toxicity toward the MCF-10a cell lines compared with cancer cell lines. [ 209 ] 2 Fe 3 O 4 @MOF-DOX h -CDs i -Apt j MDA-MB-231 Treated HUVEC cells exhibited high viability (∼90%) and no toxicity. Fe 3 O 4 @MOF-DOX-CDs-Apt prevented the cell proliferation, more than 77% selective apoptosis of MDA-MB-231 at 24h and less than 10% apoptosis of normal HUVEC cells.…”
Section: Nanobioconjugatesmentioning
confidence: 99%
“…MAHfMOF-PFP-Ni-Zn and MA-HfMOF-PFC-Ni-Zn displayed low toxicity toward the MCF-10a cell lines compared with cancer cell lines. [ 209 ] 2 Fe 3 O 4 @MOF-DOX h -CDs i -Apt j MDA-MB-231 Treated HUVEC cells exhibited high viability (∼90%) and no toxicity. Fe 3 O 4 @MOF-DOX-CDs-Apt prevented the cell proliferation, more than 77% selective apoptosis of MDA-MB-231 at 24h and less than 10% apoptosis of normal HUVEC cells.…”
Section: Nanobioconjugatesmentioning
confidence: 99%
“…62 A recent study also showed that the pyrrolidine-fused chlorin of 5,15-bis(4-methyloxycarbonylphenyl)-10,20bis-(pentafluorophenyl)porphyrin, incorporated into a metal−organic framework (MOF) functionalized with maltotriose, could efficiently target cancer cells with preferential uptake into pancreatic and breast cancer cell lines. 63 The use of chlorins and isobacteriochlorins obtained from the reaction of porphyrins and ylides as PSs in the photoinactivation of microorganisms was also considered in different studies. In 2012, Costa et al, 64 reported the synthesis and the photodynamic action of the pentacationic chlorin 55 (Figure 14) towards two antibioticresistant bacterial strains, Staphylococcus aureus and Pseudomonas aeruginosa.…”
Section: Figure 12mentioning
confidence: 99%
“…The synthetic bioinspired complexes resemble in structure, central atoms, and properties the most common naturally occurring biomolecules such as hemoglobin which transports oxygen in animal bodies, chlorophyll which acts as a light-scavenging antenna in photosynthesis inside plants, or vitamin B 12 which is important for metabolism in the cells ( Figure 2 , Table 1 ) [ 20 ]. The combination of such favorable properties makes artificial metalloporphyrins highly suited for applications in photosynthesis [ 21 ], electrochemical [ 22 ], biosensing [ 23 ], biomedical [ 24 ] applications for tumor therapy [ 25 ] and bioimaging [ 26 ].…”
Section: Introductionmentioning
confidence: 99%